Online Media and Students’ Pro-Environment Engagement- Raising Awareness, Facilitating Environment-Friendly Behavior and Social Capital: Sanaa Mirza,Faiza Latif, Asifa Kamal - Sanaa Mirza, Faiza Latif & Asifa Kamal (PJDOL, 2023)
Abstract The functioning of online media as a tool imparting awareness about environmental issues of Pakistan requires attention from academia. Therefore, the present article explains the way students use online media to engage with environment related issues of Pakistan. A carefully constructed survey using a 5-point Likert scale was administered to 223 students of Lahore who were selected through simple random sampling technique. Using Kendall’s Tau-b test and measure of rank correlation Gamma (G or γ), association between online media engagement related to environmental issues and pro-environment offline behavior was measured.